VILLAGE EMPOWERMENT THROUGH SOCIALIZATION OF MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMEs)": LITERATURE REVIEW - Melyana R Pugu; Eddy Silamat; Silvia Ekasari (JOURNAL OF COMMUNITY DEDICATION, 2024)
Empowering rural communities through increasing the capacity and accessibility of micro, small, and medium enterprises (MSMEs) is an important effort to measurably improve the economy and welfare of rural residents. This research uses the method of analyzing the latest data on the social and economic conditions of the village. The results of the study reveal that; first, the potential of MSMEs to create new employment opportunities, increase local income, and accelerate the transformation of the rural economy is quite significant. Reliable socialization must involve managerial assistance, easy access to funding, and the use of advanced digital solutions. Second, the role of the government and related stakeholders is crucial to support village development through MSME empowerment. Supporting policies such as training facilities, broad market access, and funding initiatives are absolutely necessary. Multi-sector cooperation between the government, education, and the business world is also important to build a conducive business ecosystem for rural entrepreneurs. Third, rural community empowerment needs to be implemented in an integrated and inclusive manner, not only boosting business establishment but also ensuring sustainability and growth. A sustainable approach to the improvement of MSMEs can strengthen the wheels of the village economy, reduce poverty, and improve the overall standard of living of rural communities.